ANATOMI KAYU GAHARU (Aquilaria malaccensis Lamk.) DAN BEBERAPA JENIS SEKERABAT - Y I Mandang; Bambang Wiyono (Jurnal Penelitian Hasil Hutan, 2002)
Anatomical characteristics of five "gaharu " wood species, Aquilaria malaccensis. Aetoxyl sympetalum. Gonystylus bancanus, Gonystylus macrophyllus, and Gyrinops versteeghii were described and compared, to find out how to identify and differentiate gaharu wood by their taxa. The knowledge of the difference between Aquilaria malaccensis, which has been listed in Appendix II CITES. from other gaharu wood that have not been listed, would be advantages in supporting the conservation of A. malaccensis as well as in promoting the utilization of the other gaharu wood species.The result of study indicated that all gaharu wood examined have several same features: 1) fibers with distinctly bordered pit at radial face and tend to be arranged in two series: 2) intervessel pit small, .4-7 microns: 3) rays of commonly uniseriate. Both Aquilaria malaccensis and Gyrinops versteeghii have included phloem, while the other three gaharu wood species do not contain included phloem. Aquilaria malaccensis that has been listed in Appendix II CITES could be differentiated from Gyrinops versteeghii based on vessel characteristics. aquilaria malaccensis has medium vessel diameter, 100-200 microns, frequency less than 10 vessels per sq. mm. and radial multiples of 2-4 cells. Gyrinops versteeghii has moderately small vessel diameter, less than 100 microns, frequency more than 10 vessels per sq. mm, and radial multiples of 2 -6 cells.Aetoxylon sympetalum and Gonystylus spp. are together characterized by the presence of aliform and confluent parenchyma and the occurrence of prismatic and styloid crystals in ray tissue. The presence of very thick walled fibers and rays of 1-2 to 3 seriate wide, could be used to differentiate Actoxylon sympetalum from Gonystylus spp. The latter have fibers of medium thickness and rays of commonly uniseriate.